The Erodibility of some Ghanaian Soils in Relation to their Physical and Chemical Properties. - Teye-Mensah, R. (University of Ghana, 1997)
The erodibility of soils from six different rainfall erosivity areas in Ghana were investigated. The soils were sampled and packed into wooden boxes maintained at 9% slope. Soil erosion was measured by applying simulated rainfall storms over the soil samples. The erodibility factor K for each soil type was calculated from USLE, K=A/EI30LSCP. The results showed a variability in erodibility factor values which ranged from 0.36 to 0.62. The physical and chemical properties of the soils were also measured and correlated with K values using regression techniques. The statistical analysis showed that the most important properties which related and predicted the K values for the soils studied were, permeability , pH and percentages of fine sand, clay and very fine sand.
Thesis (MPhil) - University of Ghana, 1997